Pendugaan Umur Simpan Bumbu Kuah Bakso Serbuk dengan Metode Akselerasi - Feri Kusnandar; Astri Hermeinasari; Dede Robiatul Adawiyah (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2016)
The ready to eat meat-ball seasoning powder packaged in a metalized plastic experienced gradual quality deterioration due to moisture absorption or chemical reaction. The physical moisture absorption caused product agglomeration, while the chemical reaction caused color and sensory quality changes. The aim of this research was to estimate the shelf-life of meat-ball seasoning powder using two accelerated methods, i.e. a critical moisture model and Arrhenius model. Meat-ball seasoning powder had water activity value (aw) of 0.474 and critical moisture content of 0.0369 g H2O/g dry solid. It obeyed GAB moisture sorption isotherm curve model (type II). Based on a modified critical moisture model, the product had a shelf-life of 12.1 months at relative humidity of 75%. Based on Arrhenius model for colour parameter of product solution with quality limit value of 4.15, its shelf-life at the same storage temperature and relative humidity as that of the critical moisture model was 4.0 months. The result suggested that the product deterioration due to chemical reaction occured more rapidly than that of moisture absorption.